Evaluating the World Health Organization’s Hearts Model for Hypertension and Diabetes Management: A Pilot Implementation Study in Guatemala - Irmgardt Alicia Wellmann; Luis Fernando Ayala; Taryn M. Valley; Vilma Irazola; Mark D. Huffman; Michele Heisler; Peter Rohloff; Rocío Donis; Eduardo Palacios; Manuel Ramírez-Zea; David Flood (Global Heart)
Background: The World Health Organization HEARTS Technical Package is a widely implemented global initiative to improve the primary care management of cardiovascular disease risk factors. The study’s objective is to report outcomes from a pilot implementation trial of integrated hypertension and diabetes management based on the HEARTS model in Guatemala. Methods: We conducted a single-arm pilot implementation trial over six months from October 2023 to May 2024 in 11 Guatemalan Ministry of Health primary care facilities in two districts. The pilot evaluated a package of five HEARTS-aligned implementation strategies to improve the pharmacological treatment of hypertension and diabetes. The primary outcomes were feasibility and acceptability, measured through 20 structured interviews with Ministry of Health employees and by examining enrolment and retention data. Secondary outcomes included a suite of implementation and clinical outcomes, including treatment rates. When baseline data were available, we analyzed secondary outcomes as the net change from baseline or using an interrupted time series approach. Results: The study enrolled 964 patients, of whom 58.8% had hypertension only, 30.4% had diabetes only, and 10.8% had both conditions. Surveys on feasibility and acceptability among Ministry of Health staff had a median score of 5.0 (IQR: 5.0 to 5.0) and 5.0 (IQR range: 4.8 to 5.0), respectively, exceeding the prespecified benchmark of ≥3.5. Both districts achieved the prespecified benchmark of enrolling ≥25 hypertension patients and ≥25 diabetes patients. Only 36% of patients attended a follow-up visit within three months, lower than the prespecified benchmark of ≥75%. Monthly treatment rates during the pilot increased by 22.3 (95% CI: 16.2 to 28.4; P < 0.001) and 3.5 (95% CI: –1.6 to 8.7; P = 0.17) patients per month for hypertension and diabetes, respectively. Conclusions: Implementation of an integrated hypertension and diabetes model based on HEARTS was generally feasible and acceptable in the Ministry of Health in Guatemala. Findings can refine national scale-up in Guatemala and inform HEARTS implementation projects in other settings.